Simultaneous treatment for anal fissure and hemorrhoids - J.P. Feleshtynsky; A.J. Noyes (Хірургія дитячого віку, 2023)
When using surgical approach to treatment for combined anal fissure and hemorrhoids doctor always faces the question of whether to divide the procedure into two sequential stages or to perform a simultaneous surgical intervention, and in which cases one or the other should be done.